Assessment of cold stress in crossbred cattle by wind chill temperature index - J H BUTT; D KONWAR; B BRAHMA; A KHAN; D CHAKRABORTY (Indian Journal of Animal Sciences, 2022)
In the present experiment we studied the effect of cold stress as assessed by Wind Chill Temperature (WCT) on physiological, hemato-biochemical, behavioural parameters and milk production of crossbred cattle. The study spanned for a period of 14 weeks (November to March) with WCT range of 13.51±1.09 to 5.67±0.51. The rectal temperature (°C) and respiration rate (p<0.01, r=0.812) of the experimental animals showed positive correlation with WCT while pulse rate was negatively correlated (P<0.05; r= -0.639) with WCT. There was no effect of WCT on hematobiochemical parameters with exception of AST, ALT and GPx. Feed intake (DM basis), water intake and rumination number were negatively correlated with WCT. Milk yield (kg) showed positive correlation (p<0.01; r=0.943) with WCT and dropped by 66.59% at lowest WCT. Regression analysis of data revealed high dependency of rectal temperature, respiration rate, milk yield and dry matter on WCT. The study concluded that cold stress is evident in crossbred at WCT range of 5.67±0.51 to 16.01±0.72°C.